Navigating Problem-Based Learning in English Teaching in a Low-Tech Environment: A Case Study - Indah Werdiningsih; Anita Fatimatul Laeli; Novanda Elsa Ramanida Husein (Universitas Islam Negeri Palopo, 2025)
This study explores the implementation of Problem-Based Learning (PBL) in vocational high schools operating within low-technology environments. Conducted as a qualitative case study in a private vocational institution in rural Jember, Indonesia, the research specifically investigates the strategies and challenges faced by English teachers when applying PBL without adequate technological support. Data were collected from six English teachers through semi-structured interviews and open-ended questionnaires, all of whom had at least ten years of teaching experience and were familiar with PBL-oriented instruction. The findings reveal that teachers consistently demonstrated strong adaptability and creativity despite limited access to digital tools such as projectors, internet connectivity, or multimedia resources. Several low-tech instructional strategies emerged, including the use of printed case materials, real-life problem-solving activities, paper-based dictionaries, and collaborative group discussions. Approximately 70% of teachers reported relying heavily on printed materials to replace digital media, while more than half noted that vocabulary-focused techniques were essential to support students with limited digital literacy. These adaptations illustrate high levels of teacher agency and pedagogical resilience in maintaining the quality of instruction under technological constraints. The study concludes that PBL can still be effectively implemented in low-tech classrooms through context-responsive innovation and collaborative teacher practices. These insights offer practical implications for educators, policymakers, and teacher training institutions seeking to strengthen instructional quality in resource-constrained settings. However, the study is limited by its small sample size and its focus on a single school context, indicating the need for further research across broader vocational environments.